The fundamentals of printed textile design - Russell, Alex (Bloomsbury Visual Arts, 2022)
This title explores contemporary practice in printed textile design. It provides an introduction to the creative skills, techniques and processes required by designers in order to produce a professional, creative and commercially aware portfolio
Keywords: Textile design; Textile printing; Art portfolios; Textile design -- Vocational guidance; Textile printing -- Vocational guidance